(v-1)(v+7)=

Simple and best practice solution for (v-1)(v+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (v-1)(v+7)= equation:


Simplifying
(v + -1)(v + 7) = 0

Reorder the terms:
(-1 + v)(v + 7) = 0

Reorder the terms:
(-1 + v)(7 + v) = 0

Multiply (-1 + v) * (7 + v)
(-1(7 + v) + v(7 + v)) = 0
((7 * -1 + v * -1) + v(7 + v)) = 0
((-7 + -1v) + v(7 + v)) = 0
(-7 + -1v + (7 * v + v * v)) = 0
(-7 + -1v + (7v + v2)) = 0

Combine like terms: -1v + 7v = 6v
(-7 + 6v + v2) = 0

Solving
-7 + 6v + v2 = 0

Solving for variable 'v'.

Factor a trinomial.
(-7 + -1v)(1 + -1v) = 0

Subproblem 1

Set the factor '(-7 + -1v)' equal to zero and attempt to solve: Simplifying -7 + -1v = 0 Solving -7 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1v = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1v = 0 + 7 -1v = 0 + 7 Combine like terms: 0 + 7 = 7 -1v = 7 Divide each side by '-1'. v = -7 Simplifying v = -7

Subproblem 2

Set the factor '(1 + -1v)' equal to zero and attempt to solve: Simplifying 1 + -1v = 0 Solving 1 + -1v = 0 Move all terms containing v to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1v = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1v = 0 + -1 -1v = 0 + -1 Combine like terms: 0 + -1 = -1 -1v = -1 Divide each side by '-1'. v = 1 Simplifying v = 1

Solution

v = {-7, 1}

See similar equations:

| 23-(-6z-9)+11z=7-9z | | 2r^2-7r-16=0 | | -7(-8k+1)=-343 | | 3x+3(-6x+12)=186 | | 14=5x-6 | | 2x^2-7r-16=0 | | 8=x/-5+5 | | 6n+21=4n+57+2n | | Ln(n^2+12)=ln(-9n-2) | | 3k-6+2k=12+8k-33 | | -4x-18=-(4x+2) | | 3/2+3/4 | | 8+4y=12 | | 65x=55x+100 | | m-14/9=-27 | | 4k+11+2k=-5-27k-3 | | 4x+16=4(x+4) | | 11/2+3/4 | | 3=-6n-9 | | 3(4-x)-22=x+48 | | 99x^8+63x^5-45x^2= | | -3+4(-6y-2)=4(2y-1)+3 | | y-10=-1(x-4) | | -25y+25y=-(22y+15)+10+22 | | 3x-10=5x+14 | | -33k=19 | | B+(-11)=6 | | x/3+7=11 | | -2*(-8)+4y=-8 | | -12(m-4)=240 | | -2m+8=4 | | -1v-6= |

Equations solver categories